Características dos componentes não carcaça, qualidade da carcaça e da carne de cordeiros alimentados com níveis crescentes de bagaço de azeitona - Leite, Gabriela Souza (2021)
This work was carried out to evaluate the influence of including increasing levels of olive pomace on carcass characteristics, non-carcass components, proximate composition and instrumental characteristics of meat from confined lambs. Thirty-five uncastrated male lambs from a cross between Texel and Ile de France breeds were used, weaned at 55 ± 5 days of age and, after weaning, kept in individual pens. The animals were distributed in a completely randomized design and the treatments consisted of five different levels of inclusion of olive pomace in the diet in place of corn silage, being 0%, 7.5%, 15%, 22.5% and 30 % based on dry matter. Diets were formulated to be isoprotein containing 18.81% protein. The concentrate was composed of disintegrated corn, soybean meal, calcitic limestone and mineral salt. The animals were slaughtered when they reached 35 kg of live weight, which corresponds to 60% of the adult live weight of their mothers. Hot and cold carcass yields decreased concomitantly with the increase of bagasse content in the diet (P<0.05), as well as ribeye area. The mean values for percentages of the different commercial cuts and the proximate composition were not affected by the inclusion levels of BA (P>0.05). In the non-carcass components, kidney and heart fats increased linearly with the increase in the inclusion of olive pomace, such as the testicles of the animals, while the kidneys, liver and skin had an inverse tendency to the inclusion levels, decreasing accordingly, with the increase (P<0.05). The total gastrointestinal content, the full rumen and the rumen content also increased linearly with the increase of the olive pomace in the diet, having a direct relationship with the hot and cold carcass yields (P<0.05). The pH (24hs) and temperature of the meat, cooking losses and shear force were not significantly influenced by the diet (P>0.05), while thawing losses increased according to the diet (P<0.05). Regarding the color of meat and fat, the increased levels of inclusion of olive pomace in the diet significantly influenced (P<0.05) the values of a* (intensity of red) and b* (intensity of yellow) in the observations of meat and the values of L* (brightness) and a* (intensity of red) in the observations of subcutaneous fat. Therefore, the increasing inclusion of olive pomace (BA) in replacement of corn silage in the diet of lambs, from a productive point of view, is viable up to the highest level (30%) of inclusion.